2021
DOI: 10.1021/acs.jpcc.1c00327
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation of Dyes in Graphene Oxide Thin Films and Membranes

Abstract: Intercalation of dyes into thin multilayered graphene oxide (GO) films was studied by neutron reflectivity and X-ray diffraction. Methylene blue (MB) penetrates the interlayer space of GO in ethanol solution and remains intercalated after the solvent evaporation, as revealed by the expansion of the interlayer lattice and change in chemical composition. The sorption of MB by thin GO films is found to be significantly stronger compared to the sorption of Crystal violet (CV) and Rose bengal (RB). This effect is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…The result indicated that the CT60/GO membrane has a stable separation performance. However, the XRD result indicated that the d -spacing of the membrane increased to 12.3 Å (Figure S10), which was potentially due to the invasion of dye molecules into the gap between GO nanosheets. , Figure c compares the CT60/GO membrane with prevailing GO-based membranes in terms of pure water permeance and MB selectivity. ,,, Moreover, the performance of the CT/GO membrane was also compared against membranes based on other nanomaterials, such as MXene and covalent organic frameworks (COFs), as shown in Table S5. The pure water permeance of the CT60/GO membrane was 171.5 L m –2 h –1 bar –1 and the MB rejection was 96.2%, suggesting the superior water permeance of the CT60/GO membrane and its application feasibility for dye separation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The result indicated that the CT60/GO membrane has a stable separation performance. However, the XRD result indicated that the d -spacing of the membrane increased to 12.3 Å (Figure S10), which was potentially due to the invasion of dye molecules into the gap between GO nanosheets. , Figure c compares the CT60/GO membrane with prevailing GO-based membranes in terms of pure water permeance and MB selectivity. ,,, Moreover, the performance of the CT/GO membrane was also compared against membranes based on other nanomaterials, such as MXene and covalent organic frameworks (COFs), as shown in Table S5. The pure water permeance of the CT60/GO membrane was 171.5 L m –2 h –1 bar –1 and the MB rejection was 96.2%, suggesting the superior water permeance of the CT60/GO membrane and its application feasibility for dye separation.…”
Section: Resultsmentioning
confidence: 99%
“…However, the XRD result indicated that the dspacing of the membrane increased to 12.3 Å (Figure S10), which was potentially due to the invasion of dye molecules into the gap between GO nanosheets. 42,43 Figure 5c compares the CT60/GO membrane with prevailing GO-based membranes in terms of pure water permeance and MB selectivity. 21,36,40,44−53 Moreover, the performance of the CT/GO membrane was also compared against membranes based on other nanomaterials, such as MXene and covalent organic frameworks (COFs), as shown in Table S5.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…GO with a prominent number of holes and defects on the surface). 17,26–28 The number of carbonyl and carboxylic groups, mainly located at the defect edges, increased directly with the number of holes. 17…”
Section: Introductionmentioning
confidence: 99%
“…GO with a prominent number of holes and defects on the surface). 17,[26][27][28] The number of carbonyl and carboxylic groups, mainly located at the defect edges, increased directly with the number of holes. 17 The key role of surface chemistry in the adsorption properties is also proved by the studies of selectivity and efficiencies of functionalized graphene-based sorbents, in comparison with unmodified graphene.…”
Section: Introductionmentioning
confidence: 99%
“…The study of such processes has been intensively carried out [20,21]. For example, fluorescence quenching of polymers by reduced graphene oxide [22], resonant energy transfer from a dye molecule to graphene [23], and interaction of graphene sheets with a dye using fluorescence quenching microscopy [24] have been reported.…”
Section: Introductionmentioning
confidence: 99%